Scalable, Highly Pure, and Diameter‐Sorted Boron Nitride Nanotube by Aqueous Polymer Two‐Phase Extraction (Small Methods 4/2023). Issue 4 (20th April 2023) - Ko, Jaehyoung; Kim, Daeun; Sim, Giho; Moon, Se Youn; Lee, Sang Seok; Jang, Se Gyu; Ahn, Seokhoon; Im, Sung Gap; Joo, Yongho
Abstract : Back Cover In article number 2201341, Sung Gap Im, Yongho Joo, and co‐workers demonstrate the successful separation of nanotubular boron nitrides from synthetic mixtures via an aqueous extraction protocol. The method utilizes selective partitions into thermodynamically driven phases of aqueous polymers. The method features simplicity, cost‐effectiveness, and scalability, with the resulting product demonstrating a liquid crystalline grade nanotubular assembly.